Enhancing Chinese EFL Students' Grit: The Impact of Teacher Stroke and Teacher-Student Rapport - Yuan, Lingjie (Frontiers in Psychology, 2022)
Due to the important role that students’ grit plays in the effectiveness of their success in the educational system in which they are engaged, the current study scrutinized whether some factors regarding teachers such as their stroke and rapport can affect the learners’ grit in one hand and on the other hand whether these factors can predict the learners’ grit or not. To this end, a group of 316 Chinese university English as a Foreign Language (EFL) learners from more than 30 cities from nine provinces of China were asked to fill out the three scales, namely, teacher stroke, student rapport, and students’ grit questionnaires. The foremost findings of the study, gained through running regression, indicate that there are positive relations between these variables as they affect learners’ grit and also both variables were the predictors of grit, while teacher stroke was a better predictor, uniquely clarifying 45.5% of the grit’s variance and teacher-student rapport similarly showed to be a predictor of grit, distinctively clarifying 4.6% of its variance. Accordingly, based on these findings, it can be concluded that both of these factors, as instances of positive teacher interpersonal behaviors, develop learners’ grit in language learning. In addition, this study can provide further implications and recommendations for language teaching team members in academic circumstances.